PROBLEMATIKA PENEGAKKAN HUKUM PADA UNDANG-UNDANG NOMOR 4 TAHUN 2009 TENTANG PERTAMBANGAN MINERAL DAN BATUBARA - Yahman Yahman (Arena Hukum, 2013)
AbstractEnforcement of law against illegal mining, mineral and coal in particular experience obstacles in terms of storage confiscation of evidence. An actor burdened cost of storage of evidence or known as